How many centimeters are in 1 mile? Use the equalities 1 mile = 5280 feet; 1 foot = 12 inches; and 1 centimeter = 0.394 inches. Student Selected Incorrect A. 5280 ∕ (12 x 0.394) cm Disabled B. 5280 x 12 x 0.394 cm Disabled C. (5280 x 12 ∕ 0.394) cm Disabled D. (5280 + 12 + 0.394) cm
How do I describe the translation in terms of x and y?
You shift every point 6 units to the right and 6 units down. Check out the attached image below. In that image, I show point A moving to point A' in this fashion. Every other point (B and C) will move along this similar pattern. This is how the triangle ABC moves to A'B'C'
------------------------------------
In terms of an algebraic rule, it would be (x,y) --> (x+6, y-6). We add 6 to the x coordinate of each point. At the same time, we subtract 6 from each y coordinate.
For instance, A is at (-2,3). Add 6 to the x coordinate and we get (4,3). Now subtract 6 from the y coordinate and we end up with A' = (4,-3). Points B and C will be treated in a similar manner.
Note: Triangle ABC is called the pre-image ("pre" meaning "before") while A'B'C' is called the image.
If interest compound at 20% per year how long will it take 50000 to accumulate to 86400
To find the time it takes for an amount to accumulate with compound interest, we can use the formula A = P(1 + r/n)^(nt). In this case, it will take approximately 2.56 years for $50000 to accumulate to $86400 with a 20% compound interest rate.
Explanation:To find the time it takes for an amount to accumulate with compound interest, we can use the formula:
A = P(1 + r/n)^(nt)
where:
A is the final amountP is the principal (initial amount)r is the interest rate (in decimal form)n is the number of compounding periods per yeart is the time in yearsIn this case, we have:
50000(1 + 0.20/1)^(1*t) = 86400
Dividing both sides of the equation by 50000, we get:
(1 + 0.20)^t = 1.728
Using logarithms, we can solve for t:
t = log(1.728) / log(1.20)
t ≈ 2.56
Therefore, it will take approximately 2.56 years for $50000 to accumulate to $86400 with a 20% compound interest rate.
Learn more about Compound Interest here:https://brainly.com/question/34614903
#SPJ3
Amy made the following conjecture: When any number is multiplied by itself, the product will be greater than this starting number.
For example: in 2x2=4, the product 4 is greater than the starting number 2.
Megan disagreed with Amy's conjecture, however,
[tex] \frac{1}{2 } \times \frac{1}{2} = \frac{1}{4} [/tex]
and
[tex] \frac{1}{4} [/tex]
is less than
[tex] \frac{1}{2} [/tex]
how could Amy's conjecture be improved? Explain the change(s) you would make
Amy's conjecture can be improved by including a limit. Since any number greater than one multiplied by itself will be greater (for example, 2x2 = 4). But, any number less than one (excluding zero, but including negatives) will yield a smaller result.
Amy's conjecture should be
"When a number greater than 1 is multiplied by itself, the product will be greater than the starting number,"
11 15/26 + [-17 5/13] =
11 15/26 + [-17 5/13] =
[tex]11 \frac{15}{26} = \frac{301}{26}[/tex]
[tex]-17 \frac{5}{13} = -\frac{226}{13}[/tex]
[tex]\frac{301}{26} - \frac{226}{13}[/tex]
To subtract two fractions the denominators should be same
Least common denominator = 26
We multiply second fraction by 2
[tex]\frac{301}{26} - \frac{452}{26}[/tex]
[tex]\frac{301-452}{26}[/tex]
[tex]\frac{-151}{26}[/tex]
Two of the angles in a triangle measure 23° and 8°. What is the measure of the third angle?
The 3 inside angles of a triangle equal 180 degrees.
You are given 23 and 8 for two of them.
Subtract the 2 given angles from 180 to find the 3rd angle.
3rd angle = 180 -23 - 8 = 149 degrees.
i hate math. Expand 4(-2y + 3).
i think its -8y + 12
Answer:
-8y + 12
Step-by-step explanation:
Which relation is a function?
Its the one shaped like a V
How much would it cost to buy 3 medium sodas and 2 hot dogs
To start off you need to figure out how much money each item costs. Now get out your calculator because it will make this process go much faster.
EXAMPLE:
If your sodas cost $2.25 EACH you need to do the following math equation
2.25 X 3 = 6.75 witch is the total you would be paying in this situation.
HOT DOGS EXAMPLE:
Lets say that your hotdogs are $4.75 PER DOG. You just need to follow the same steps above.
4.75 X 2 = 9.5 but thats not how we write money so it would be $9.50
Hope this helps,
Daniel
Answer:
depends what price it is
Step-by-step explanation:
In 2 hours the minutes hand of a clock rotates through an angel of how many degrees?
Yes it definitely is 720 degrees.
1 round= 360 degrees
2 rounds= 2 X 360 = 720 degrees
:-)
3 over 4+(-2 1 over2)
¾ + ( - 2 ½) = - 1 ¾
Write an expression for the perimeter of the triangle shown below: A triangle is shown with side lengths labeled 2.3x plus 14, 2x, and negative 0.2x plus 15.
A: 4.1x + 29
B: 4.1x - 29
C: 4.5x+ 29
D: 4.5x -29
Answer:
A because you can only add values with the same variable. You add 2.3x plus 2x which gives you 4.3x then you subtract .2x which gives you 4.1. Lastly you add 15 and 14 which gives you 29
Step-by-step explanation:
A web site charges $0.99 to download a game and a 12.49 membership fee.write an expression that gives the total cost in dollars to download a g games
Hello!
To write this equation we will use c to represent the total cost, and g to represent however many games you download.
c=12.49+0.99g
The constant rate is 12.49, that will never increase or change in our equation.
Depending on how many games you download, that will be the rate that affects our total cost.
If you only purchase one game, you only spend $13.48. Where as if you buy 10 games, you spend $22.39.
Multiply. What is the value of the second partial product? 26 × 107
the product
26 x 107=2,782
Answer:
2782
Step-by-step explanation:
What measures acceleration
I mean - accelerometers do, are you sure this is the correct place to post this question?
Please help will give brainliest
Answer:
James and Logan each are eating sandwiches. Logan finished his but then stole 1/3 of James' sandwich. James still has 5 times the parts of his sandwich then Logan. What fraction of a sandwich does Logan still have left?
Step-by-step explanation:
Logan stole 1/3 of James' sandwich resulting in Logan owning James 1/3 of a sandwich.
slope intercept of (2,1) and (4,0)
Dwayne earns $11.45 per hour. Last week he worked 38-1/4 (mixed number) hours. How much did he earn last week?
Okay this is simple.
We willl use this equation
$11.45×38.25=X
If you do this problem you should get $437.96 as an answer
*Remember that fractions can be changed to decimals. Fractions mean division.
A quadratic function has a line of symmetry at x=-3.5 and zero at -9 what is the distance from the given zero to line of symmetry
If a quadratic function has zero at x=-9, then point (-9,0) lies on the graph of quadratic function.
A line of symmetry has equation x=-3.5 that is x+3.5=0.
Use formula for the distance from point [tex](x_0,y_0)[/tex] to the line AX+By+C=0:
[tex]d=\dfrac{|Ax_0+By_0+C|}{\sqrt{A^2+B^2}}.[/tex]
Thus,
[tex]d=\dfrac{|-9+3.5|}{\sqrt{1^2+0^2}}=5.5.[/tex]
Answer: the distance is 5.5 units.
Answer:
5.5
Step-by-step explanation:
PLEASE help me and PLEASE show the work PLEASE.
20(4×-2)
________
(4 - (-2))²
simplified;
20(-8)
_____
(6)²
simplified;
-160
______
36
simplified;
-4 16/36
simplified;
-4 4/9
A car rental company charges a $25.00 base fee plus $0.10 per mile driven to rent a car. How many miles did a customer drive if the customers bill was $37.80? Write the variable represents, equation, and miles.
Answer:
128 miles
Step-by-step explanation:
Given that a car rental company charges a $25.00 base fee plus $0.10 per mile driven to rent a car.
Let us represent y as total charges and x no of miles driven
Even if x=0, y= 25 (base fee)
SO y intercept =25
Slope = charge per drive = 0.10
So equation is
y =0.1x +25
To find out how many miles did a customer drive if the customers bill was $37.80, we can use the above equation.
y = 37.80 and x =?
37.80=0.1x+25
0.1x = 12.80
x = 12.80/0.1 = 128 miles
35. One expressed power of Congress stated in the Constitution is the power to a. coin money b. create treaties. c. create schools. d. establish prisons.
Estimate the product of 76 × 46 by rounding both numbers to the nearest ten before multiplying.
4000. 76 rounds to 80 and 46 rounds to 50 so 80 x 50 is 4000
What are the x and y intercepts of the line 3x-4y=12
x-intercept = 4, y-intercept = - 3
to find the intercepts, that is where the graph crosses the axes
let x = 0, in the equation for y- intercept
let y = 0, in the equation for x- intercept
x = 0 : - 4y = 12 ⇒ y = - 3 ⇒ (0, - 3) ← y - intercept
y = 0 : 3x = 12 ⇒ x = 4 ⇒ (4, 0 ) ← x- intercept
Hey there...
So this is a tough question.....
Let's start with the x first, then we will go to y.
So, here is the x.
Explanation: To find the x intercept, make the y = (0). Since we know that x needs 0 for the y coordinate.
3x-4(0)=12
x=4.
So the intercept for x = 4.
Now we have to do the y.
Explanation: To find the y, make x = (0), since know that y needs 0 in the front of the number.
3(0)-4y=12
y=-3
So the y = -3.
Hope this helps.....
1. Margot hiked around lake C each day. How many miles did she hike in 12 days?
2. Keenan hiked 15 times as far as Margot. How far did Keenan hike?
1. 252 beacuse 21 x 12= 252
2. 3780 Now 252 x 15=3780
Using the multiplication operation, the number of miles hiked by Margot and Kennan are 252 miles and 3780 miles respectively
The approximate distance around Lake C = 21 miles
Number of hiking days = 12
Hence, the number of miles hiked by Margot will be :
21 × 12 = 252 milesKeenan hiked 15 times as far as Margot :
Margot's mile × 15 Keenan's distance = 252 × 15 = 3780 milesTherefore, the Number of miles hiked by Margot and Kennan are 252 miles and 3780 miles respectively
Learn more : https://brainly.com/question/18405415
What are 5 fractions that can simplify to 2/5
4/10
6/15
18/45
8/20
16/40
Angle E and angle F are vertical angles with m angle E = 5x + 10 and m angle F = 7x - 12
What is the value of X?
Vertical angles are always equal.
So you can set the equation up like this:
5x + 10 = 7x - 12
Subtract 5x from both sides. Then Add 12 to both sides.
22 = 2x
Divide both sides by 2.
11 = x
Vertical angles are equal, so we set the expressions 5x + 10 and 7x - 12 equal to each other and solve for 'x', resulting in the value of 'x' being 11.
Explanation:The student is asking about vertical angles, which are angles opposite each other when two lines cross. In this case, m angle E and m angle F are vertical angles with given expressions for their measures. According to the property of vertical angles, they are equal. This means we can set the expressions for their measures equal to each other and solve for 'x'.
The equations given are:
m angle E = 5x + 10m angle F = 7x - 12Since m angle E = m angle F, we write:
5x + 10 = 7x - 12
Now, let's solve for 'x':
Subtract 5x from both sides: 10 = 2x - 12.Add 12 to both sides: 22 = 2x.Divide both sides by 2: x = 11.So, the value of 'x' is 11.
Which shows the phrase the sum of a number and 8 is a variable expression?
n + 8
n - 8
8n + 8
8n
"The sum of" means addition
Let "a number" = n
n + 8, or (A) is your answer
hope this helps
Zoey wants to cover her bedroom floor with carpet squares each square has an area of 1 foot her bedroom measures 12 feet by 14 feet how many carpets squares does she need
Final answer:
Zoey needs 168 carpet squares to cover her bedroom floor that measures 12 feet by 14 feet, since each carpet square covers 1 square foot.
Explanation:
Zoey wants to cover her bedroom floor with carpet squares where each square has an area of 1 square foot. Her bedroom measures 12 feet by 14 feet. To find out how many carpet squares she needs, we need to calculate the total square footage of her room by multiplying its length by its width.
The calculation will be:
Length × Width = 12 feet × 14 feet = 168 square feet.
Since each carpet square covers 1 square foot, Zoey will need a number of squares that equals the total square footage of her room. Therefore:
Total square footage = Number of carpet squares needed
168 square feet = 168 carpet squares needed.
Zoey will need 168 carpet squares to cover her bedroom floor completely.
Simplify the expression. Write your answer as a power. (2/3)^2⋅(2/3)^6
(2/3)^2⋅(2/3)^6 = (2/3)^(2+6) = (2/3)^8
When we have the same thing being multiplied by itself with a different exponent on it, we add the two exponents.
(a^b)*(a^c) = a^(b+c)
Final answer:
The simplification of the expression [tex](2/3)^2\times (2/3)^6[/tex] is obtained by adding the exponents, resulting in [tex](2/3)^8[/tex].
Explanation:
To simplify the expression[tex](2/3)^2\times (2/3)^6[/tex], we need to remember the rule of exponents which states that when we multiply two powers with the same base, we add the exponents. So in this case, we have the base (2/3) and we will add the exponents 2 and 6 together.
[tex](2/3)^2 \times (2/3)^6 = (2/3)^{(2+6)} = (2/3)^8.[/tex]
To write the answer as a power, we simply keep the same base of 2/3 and use the sum of the exponents as the new exponent. Therefore, the simplified expression is written as a power: [tex](2/3)^8[/tex]